Influence of delta ferrite on corrosion susceptibility of AISI 304 austenitic stainless steel. Issue 1 (31st December 2016) - Osoba, Lawrence O.; Elemuren, Raheem A.; Ekpe, Ikenna C.
Abstract: In the current study, the influence of delta (δ) ferrite on the corrosion susceptibility of AISI 304 austenitic stainless steel was evaluated in 1Molar concentration of sulphuric acid (H2 SO4 ) and 1Molar concentration of sodium chloride (NaCl). The study was performed at ambient temperature using electrochemical technique—Tafel plots to evaluate the corrosive tendencies of the austenitic stainless steel sample. The as-received (stainless steel) specimen and 60% cold-worked (stainless steel) specimens were isothermally annealed at 1, 100°C for 2 h and 1 h, respectively, and quenched in water. The results obtained show that the heat-treated specimen and the 60% cold-worked plus heat-treated specimen exhibited higher corrosion susceptibility than the as-received specimen, which invariably contained the highest fraction of δ ferrite particles. The finding shows that the presence of δ ferrite, in which chromium (Cr), the main corrosion inhibitor segregates, does not degrade and or reduces the resistance to aqueous corrosion of the austenitic stainless steel material.